2018
DOI: 10.1007/s10997-018-9404-1
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and the performance of governance functions between a board, management and other stakeholders: the case of Robotdalen

Abstract: Previous research has called for an enhanced understanding of the dynamic and interactional aspects of board work in public sector governance. Using a longitudinal case study of Robotdalen, this paper attempts to meet this call through a processual and qualitative study of board work in public organisations. The aim of the paper is to enhance our understanding of the human side of governance and the interactions between a board, the management in the governed organisation and other stakeholders. We do this by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…These tensions are important to consider because board and organization often tend to have different expectations for their roles and tasks (Brennan, 2006). Expectation is related to the concept of trust (Nooteboom et al, 1997;Höglund et al, 2018). Previous research has shown that to understand the relationships between the governed organization and board, trust is essential (Huse and Zattoni, 2008) and that trust development is crucial for organizational performance (Brennan, 2006).…”
Section: Governing Board and Trustmentioning
confidence: 99%
“…These tensions are important to consider because board and organization often tend to have different expectations for their roles and tasks (Brennan, 2006). Expectation is related to the concept of trust (Nooteboom et al, 1997;Höglund et al, 2018). Previous research has shown that to understand the relationships between the governed organization and board, trust is essential (Huse and Zattoni, 2008) and that trust development is crucial for organizational performance (Brennan, 2006).…”
Section: Governing Board and Trustmentioning
confidence: 99%
“…We recognize that BoDs meet relatively rarely, and that could limit their ability to develop informed perceptions of the constructs in question (Podsakoff et al, 2012;Zattoni et al, 2015). Further research might address this limitation by relying on ethnographic techniques, which would make it possible to investigate live activities and behavior inside and outside the boardroom on a longitudinal basis and from an individual-level perspective (Höglund et al, 2018;Hoppmann et al, 2019;Sievinen et al, 2020). Importantly, such techniques might be especially fruitful regarding the ownership-related differences in board behavior and their impact on EO.…”
Section: Limitations and Future Researchmentioning
confidence: 99%